1997
DOI: 10.1037/0894-4105.11.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the roles of the hippocampus complex and the neocortex in long-term memory storage: Evidence from the study of semantic dementia and Alzheimer's disease.

Abstract: Several computational models suggest that the hippocampal complex plays a key role in the establishment of new memories, but over time the storage of such memories becomes independent of this region. In support of such models, the authors demonstrate that patients with semantic dementia, who have relative sparing of the hippocampal complex, show a pattern of preserved recent memories and impaired distant memories. In a group study that used the Autobiographical Memory Interview, amnesic patients with Alzheimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
197
4
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(223 citation statements)
references
References 72 publications
19
197
4
3
Order By: Relevance
“…procedural memory) remain relatively intact, whilst others (e.g., episodic memory) are dramatically impaired (Salmon & Bondi, 2009;Pause et al, 2013). These dissociations are indeed supported also by a developing understanding of the role played by different brain areas in the cognitive processes of memory encoding, storing and retrieval (Glisky, 1998;Graham & Hodges, 1997;Nadel & Moscovitch, 1997).…”
Section: Introductionmentioning
confidence: 60%
“…procedural memory) remain relatively intact, whilst others (e.g., episodic memory) are dramatically impaired (Salmon & Bondi, 2009;Pause et al, 2013). These dissociations are indeed supported also by a developing understanding of the role played by different brain areas in the cognitive processes of memory encoding, storing and retrieval (Glisky, 1998;Graham & Hodges, 1997;Nadel & Moscovitch, 1997).…”
Section: Introductionmentioning
confidence: 60%
“…However, it is interesting to note that the memories that HM does recall tend to have a very fixed structure, which suggests that intact medial temporal lobes are necessary for the formation new associations between old memories. Additional evidence for eventual cortical consolidation of the associative memory network comes from the fact that semantic dementia patients generally have damage to the temporal poles rather than the parahippocampal region (Graham & Hodges, 1997;Mummery et al, 1999).…”
Section: The Frontal Lobesmentioning
confidence: 99%
“…Left-sided predominant atrophy is more frequent than right predominant or symmetrical involvement (e.g., [7,26,29]). Visual inspection of MRI brain scans has suggested that the hippocampal complex is preserved in SD, which might fit with normal day-to-day memory, or near normal performance on episodic memory tests in some patients [27,28,57,58]. Some authors [29,9] did not find significant atrophy of the hippocampus and adjacent structures using the SPM software which allows a voxel-by-voxel analysis (Voxel Based Morphometry, VBM) of the entire brain.…”
Section: Introductionmentioning
confidence: 99%